Community health advocacy to prevent social and health problems associated with gambling - a case study - Howat, Peter; Maycock, Bruce; Slevin, T. (The Australian Journal of Primary Health, La Trobe University, 2005)
Federal and state elections provide opportunity for health advocacy. Prior to the elections political parties reformulate their policies, many of which are relevant to public health. The adverse effects of gambling have been minimised in Western Australia (WA) compared to other states and territories in Australia due to strict policies that limit the availability of electronic gaming machines (EGMs). In the lead-up to the 2001 state election, aggressive lobbying of politicians was undertaken in an attempt to allow the expansion of poker machines to hotels and licensed clubs throughout the state. The proponents of this were representatives of the hoteliers and licensed clubs who claimed their continued economic viability was dependent on such a move. Opponents consisted of a coalition of community groups and professional associations. This paper is a summary of the approach taken by health advocates that ultimately contributed to written endorsement of the two main political parties to maintain the moratorium on the expansion of poker machines in WA. Focus of the paper is given to one approach involving direct contact with political candidates. This approach holds promise for effective advocacy for other public health issues.